1970
DOI: 10.1128/am.19.1.182-183.1970
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hypobaric and Hyperbaric Helium Atmospheres on the Growth of Chlorella sorokiniana

Abstract: Growth of Chlorella sorokiniana is unaffected by the choice of atmospheric diluent gas. Reduced total pressure has no inhibitory effect and may be slightly stimulatory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1989
1989
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Some featured (non-cyanobacterium) microalgae of the genus Chlorella. They showed no negative impact of lowering the pressure to 565 hPa 15 , and even suggested a positive impact of decreasing it to 250 hPa 16 under constant pCO2. Other low-pressure experiments included cyanobacteria.…”
Section: Introductionmentioning
confidence: 98%
“…Some featured (non-cyanobacterium) microalgae of the genus Chlorella. They showed no negative impact of lowering the pressure to 565 hPa 15 , and even suggested a positive impact of decreasing it to 250 hPa 16 under constant pCO2. Other low-pressure experiments included cyanobacteria.…”
Section: Introductionmentioning
confidence: 98%
“…Early studies of algae growth at low pressures ranging from 250 to 500 mbar suggested that low atmospheric pressures have no inhibitory effect and might slightly stimulate growth ( Orcutt et al, 1970 ). Some algae have also developed anoxic metabolisms to adapt to low oxygen conditions ( Yang et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%